Identification of Plasmodium falciparum Translation Initiation eIF2β Subunit: Direct Interaction with Protein Phosphatase Type 1 - Tellier, Géraldine; Lenne, Astrid; Cailliau-Maggio, Katia; Cabezas-Cruz, Alejandro; Valdés, James J.; Martoriati, Alain; Aliouat, El M.; Gosset, Pierre; Delaire, Baptiste; Fréville, Aline; Pierrot, Christine; Khalife, Jamal (Frontiers in Microbiology, 2016)
Protein phosphatase 1 (PP1c) is one of the main phosphatases whose function is shaped by many regulators to confer a specific location and a selective function for this enzyme. Here, we report that eukaryotic initiation factor 2 of P. falciparum (PfeIF2β) is an interactor of PfPP1c. Sequence analysis of PfeIF2 revealed a deletion of 111 amino acids when compared to its human counterpart and the presence of two potential binding motifs to PfPP1 (29FGEKKK34, 103KVAW106). As expected, we showed that PfeIF2 binds PfeIF2 and PfeIF5, confirming its canonical interaction with partners of the translation complex. Studies of the PfeIF2-PfPP1 interaction using wild-type, single and double mutated versions of PfeIF2β revealed that both binding motifs are critical. We next showed that PfeIF2 is able to induce Germinal Vesicle BreakDown (GVBD) when expressed in Xenopus oocytes, an indicator of its capacity to regulate PP1. Only combined mutations of both binding motifs abolished the interaction with PP1 and the induction of GVBD. In P. falciparum, although the locus is accessible for genetic manipulation, PfeIF2 seems to play an essential role in intraerythrocytic cycle as no viable knockout parasites were detectable. Interestingly, as for PfPP1, the subcellular fractionation of P. falciparum localized PfeIF2β in cytoplasm and nuclear extracts, suggesting a potential effect on PfPP1 in both compartments and raising the question of a non-canonical function of PfeIf2 in the nucleus. Hence, the role played by PfeIF2 in blood stage parasites could occur at multiple levels involving the binding to proteins of the translational complex and to PfPP1.